Analysis of Investment Decisions in Sharia Cooperatives: Does Sharia Accounting Standards Affect? - Khoerulloh, Abd. Kholik; Janwari, Yadi (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
Abstract: Investors in sharia cooperatives in Majalengka Regency suffered losses due to its administrators and managers who were not transparent in reporting their finances. This research aims to determine the effect of the application of sharia accounting standards and human resource competencies on investment decisions through financial reporting quality. The analytical techniques used in this study use path analysis. The results showed that the application of Sharia accounting standards had no significant adverse effect on investment decisions through financial reporting quality with an original sample value of -0.021 and Pvalue 0.554 > 0.05. In contrast, human resource competence significantly affected investment decisions through financial reporting quality with original sample values of 0.403 and Pvalue of 0.044 < 0.05. The implication of this research is to improve sharia cooperative management in financial performance to attract members to invest. The novelty of this research is the motive of investing in sharia cooperatives.Abstrak: Investor pada koperasi syariah di Kabupaten Majalengka mengalami kerugian karena ulah para pengurus dan pengelolanya yang tidak transparan dalam melaporkan keuangannya. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan standar akuntansi syariah dan kompetensi sumber daya manusia terhadap keputusan investasi melalui kualitas laporan keuangan. Teknik analisis yang digunakan dalam penelitian ini menggunakan analisis jalur. Hasilnya menunjukkan bahwa penerapan standar akuntansi syariah berpengaruh negatif tidak signifikan terhadap keputusan investasi melalui kualitas laporan keuangan dengan nilai original sample sebesar -0.021 dan Pvalue 0.554 > 0.05, sedangkan kompetensi sumber daya manusia berpengaruh positif signifikan terhadap keputusan investasi melalui kualitas laporan keuangan dengan nilai original sample sebesar 0.403 dan Pvalue 0.044 < 0.05. Implikasi dari penelitian ini adalah meningkatkan manajemen koperasi syariah dalam kinerja keuangan sehingga menarik anggota untuk berinvestasi. Kebaruan dari penelitian ini adalah motif investasi pada koperasi syariah.